Insights into future management of lupus nephritis - Askanase, Anca D.; Dall’Era, Maria; Almaani, Salem (Frontiers in Lupus, 2024)
Lupus nephritis (LN) is a common and serious manifestation of systemic lupus erythematosus and is a major cause of mortality and morbidity. The current standard-of-care treatment for LN include conventional immunosuppressive treatments such as mycophenolate mofetil, cyclophosphamide, or azathioprine, combined with glucocorticoids. However, this treatment approach has several unmet needs, such as achieving only modest remission rates, potential toxicities, and prolonged cumulative steroid exposure, resulting in suboptimal patient outcomes. The LN treatment landscape is evolving rapidly to meet these unmet needs, with belimumab and voclosporin being the first drugs approved specifically for treatment of LN in 2020 and 2021, respectively. Here, we review the likely roles in LN therapy for several targeted therapies, including select therapies under investigation, and interventions in early development such as therapies targeting B cells (obinutuzumab, atacicept, ianalumab, and CD19 chimeric antigen T-cell therapy), inflammatory cytokines (secukinumab and anifrolumab), and the immunoproteasome (zetomipzomib); we also review treatment strategies designed to minimize steroid exposure. Treatments in development have demonstrated encouraging short-and long-term efficacy and steroid-sparing potential, potentially paving the way for improved treatment regimens and patient outcomes in LN.